Culturally Responsive Computing in Urban, After-School Contexts: Two Approaches. (September 2013) - Eglash, Ron; Gilbert, Juan E.; Taylor, Valerie; Geier, Susan R.
The academic performance and engagement of youth from under-represented ethnic groups (African American, Latino, and Indigenous) in science, technology, engineering, and mathematics (STEM) show statistically large gaps in comparison with their White and Asian peers. Some of these differences can be attributed to the direct impact of economic forces. But cultural factors also play a role. This essay will examine two culturally responsive math education technologies and report on evaluations of the technologies in urban out-of-school settings that suggest both approaches can be effective for integrating math education into urban, after-school contexts.